Cardiac Function, Perfusion, Metabolism, and Innervation following Autologous Stem Cell Therapy for Acute ST-Elevation Myocardial Infarction. A FINCELL-INSIGHT Sub-Study with PET and MRI - Mäki, Maija T.; Koskenvuo, Juha W.; Ukkonen, Heikki; Saraste, Antti; Tuunanen, Helena; Pietilä, Mikko; Nesterov, Sergey V.; Aalto, Ville; Airaksinen, K. E. Juhani; Pärkkä, Jussi P.; Lautamäki, Riikka; Kervinen, Kari; et al. (Frontiers in Physiology, 2012)
Purpose: Beneficial mechanisms of bone marrow cell (BMC) therapy for acute ST-segment elevation myocardial infarct (STEMI) are largely unknown in humans. Therefore, we evaluated the feasibility of serial positron emission tomography (PET) and MRI studies to provide insight into the effects of BMCs on the healing process of ischemic myocardial damage. Methods: Nineteen patients with successful primary reteplase thrombolysis (mean 2.4 hours after symptoms) for STEMI were randomized for BMC therapy (2.9 x 106 CD34+ cells) or placebo after bone marrow aspiration in a double-blind, multi-center study. Three days post-MI, coronary angioplasty and paclitaxel eluting stent implantation preceded either BMC or placebo therapy. Cardiac PET and MRI studies were performed 7-12 days after therapies and repeated after six months, and images were analyzed at a central core laboratory. Results: In BMC treated patients, there was a decrease in [11C]-HED defect size (-4.9±4.0% vs. -1.6±2.2%, p=0.08)) and an increase in [18F]-FDG uptake in the infarct area at risk (0.06±0.09 vs. -0.05±0.16, p=0.07) compared to controls, as well as less left ventricular dilatation (-4.4±13.3 mL/m2 vs. 8.0±16.7 mL/m2, p=0.12) at six-months follow-up. However, BMC treatment was inferior to placebo in terms of changes in rest perfusion in the area at risk (-0.09±0.17 vs. 0.10±0.17, p=0.03) and infarct size (0.4±4.2 g vs. -5.1±5.9 g, p=0.047), and no effect was observed on ejection fraction (EF) (p=0.37). Conclusions: After the acute phase of STEMI, BMC therapy showed only minor trends of long-term benefit in patients with rapid successful thrombolysis. There was a trend of more decrease in innervation defect size and enhanced glucose metabolism in the infarct related myocardium and also a trend of less ventricular dilatation in the BMC treated group compared to placebo. However, no consistently better outcome was observed in the BMC treated group compared to placebo.